Analisis Tingkat Pendapatan Usaha Bakwan Mitra Abadi Di Lingkungan Nusantara Kota Bima - Megasuciati Wardani (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2023)
This research aims to analyze the Income Level of Bakwan Mitra Abadi Business in the Nusantara Neighborhood of Monggonao Village, Bima City. The research conducted in this study is descriptive research. The population in this study consists of the income data of Bakwan Mitra Abadi Business in the Nusantara Neighborhood of Monggonao Village, Bima City, for one period (12 months), which is the year 2021. The sample in this study is a saturation sample, meaning that all members of the population whose income data of Bakwan Mitra Abadi Business in the Nusantara Neighborhood of Monggonao Village, Bima City, for one period (12 months) in the year 2021 are taken as the sample. Based on data analysis using a one-sample t-test, the calculated t-value is 2.068. To test whether the hypothesis stating that the income level of Bakwan Mitra Abadi Business in the Nusantara Neighborhood of Monggonao Village is greater than or equal to Rp. 72,500,000 per month can be accepted, a one-tailed test (left-tailed test) is used. At a significance level of 5% (0.05) with degrees of freedom (df = n-1 = 12-1 = 11), the critical t-value (t-table) is 1.796. By comparing the calculated t-value (2.068) with the critical t-value (1.796), it is evident that the calculated t-value is greater than the critical t-value (2.068 ≥ 1.796).